Exploring the versatility of PLS-SEM analysis in research: from social sciences to engineering applications / Mohamad Zain Hashim and Muriatul Khusmah Musa - Hashim, Mohamad Zain; Musa, Muriatul Khusmah (Unit Penerbitan PKAPP, 2024)
Introduction Partial Least Squares Structural Equation Modeling (PLS-SEM) has emerged as a powerful statistical analysis tool, especially within the realms of social sciences and business research. Unlike traditional statistical methods, PLS-SEM focuses on maximizing the explained variance of the dependent latent constructs, making it particularly useful for complex models and when dealing with real-world data that may not meet strict assumptions of normality. Its application through software like SmartPLS has simplified the process, making advanced statistical analysis accessible to researchers and practitioners alike.